(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2023)
History education in post-apartheid South Africa addresses topics that are highly salient to the concept of race. To make sense of colonialism, slavery, the Holocaust, and most notably apartheid, students require an understanding of what race is, and how it has been used to justify discriminatory and unjust behaviour. The South African Curriculum and Policy Statements for Grade 9 History therefore devotes two hours to a topic on “the definition of race” (Department of Basic Education [DBE], 2011a: 43). However, what are students learning about ‘the definition of race’ from their history education? In this article, we draw on our experience as a history educator and history education researcher to argue that students often develop inaccurate and unhelpful understandings of race. This is partially since both the South African history curricula and textbooks describe race as a “myth” (DBE, 2011a, 43; Bottaro, Cohen, Dilley, Duffett, & Visser, 2013) with no scientific or evolutionary basis. Hence, students who learn that race is a ‘myth’ understandably struggle to understand discourses and policies that refer to racial identity and are at risk of misunderstanding theories of evolution. While we agree that the concept of race has no legitimate scientific basis, we nonetheless argue that students require an historical understanding of race; one that demonstrates how racial identities have been constructed in different ways and for different purposes over time. Such an approach would introduce students to the extensive historiography of the construction of race (e.g. DuBois, 1940; Dubow, 1995). By understanding race as a construct rather than a myth, we suggest that students will be better able to engage with the legacies of racialised violence as well as the ways in which racial identity is a legitimate source of meaning for many South Africans.